Cold stress reduces rice grain yield in temperate conditions - Rasim Unan; Temel Genctan; Rafael M. Pedroso (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the cold stress effect in natural field conditions by employing different rice sowing timings over three years, to identify national varieties tolerant to cold stress at the vegetative and generative stages, and to propose a data-derived solution regarding termination and resowing due to cold stress conditions. Early, regular, and late sowing dates were employed to capture natural cold stress conditions in a 3-year-long experiment. Sowing dates resulting in the greatest yields fluctuated from regular to late sowing dates, according to the stress duration in cold stress years. Yield losses resulting from cold stress ranged from 0.810 to 2.740 t ha-1 and reached 38.6%. ‘Halilbey,’ ‘Pasali,’ and ‘Mevlutbey’ were found to be most cold-tolerant varieties. Grain yield was correlated with plant number; the critical minimum level was between 60.8 and 79.6 plants m-2 and the optimum was 132.3 plants m-2 for economical yield. Cold stress negatively affected rice plant density, and plant densities below the critical minimum plant warranted crop termination and resowing, depending on application costs. Cold stress had a far more devastating effect on germination and seedling stages than on later development stages in temperate conditions.